A study of the Effect of Urbanization on Annual Evaporation Rates in Baghdad City Using Remote Sensing - Ali, Ali K. Mohammed; Al Ramahi, Fouad K. Mashee (Iraqi Journal of Science, 2020)
The city of Baghdad has recently witnessed an increase in urban land due to the recent economic growth, which negatively affected the environment of the study area through the retraction of the agricultural lands surrounding the city. Therefore, we studied the relationship between increasing urban expansion and changes in the local climate of Baghdad for the period from 2008 to 2018. The information derived from the satellites utilized in this search showed the changes in ground cover during the study period, while the evaporation rate data source from the European Center for Forecasting (ECMWF) confirmed the effects of urban expansion on evaporation rates. Increasing urbanization increased evaporation rates and decreased vegetation degradation (NDVI). Satellite data from Landsat )TM( and Landsat )OLI( for 2008, 2013, and 2018 were processed and analyzed using the ArcGIS program. The visuals were classified into urban land, sparse plant, dense plant, water, bare soil, and wet soil. The results of the classification showed that the percentage of urban land was 26.5%, 28.3%, and 30.9% for the years of 2008, 2013, and 2018, respectively. On the other hand, the MNDWI value for the studied years was 2.0%, 1.9% and 3.6%. The highest rate of urbanization was in 2018 which was accompanied by highest evaporation rates. The study proved that there was a significant correlation between increasing urbanization and evaporation rate in the study area. These results indicate that the poor planning of land use leads to negative effects on the local climate.